Anomalies in the Indian Stock Market - Peswani, Shilpa; Jesudasan, Smita (SFIMAR Research Review, 2019)
The paper studies three anomalies in the Indian equity market - size, value and price movement after dividend announcement. The size anomaly delivered positive returns, value anomaly has not delivered positive returns in the period of study. While the entire period average return to value anomaly is negative, maximum returns delivered by the anomaly is approximately 18%. Also, dividend announcements affect the returns reflected in the stock price changes in some days. Having said that returns to these anomalies are transitory.